2017
DOI: 10.1007/978-3-319-63387-9_15
|View full text |Cite
|
Sign up to set email alerts
|

Logical Clustering and Learning for Time-Series Data

Abstract: In order to effectively analyze and build cyberphysical systems (CPS), designers today have to combat the data deluge problem, i.e., the burden of processing intractably large amounts of data produced by complex models and experiments. In this work, we utilize monotonic parametric signal temporal logic (PSTL) to design features for unsupervised classification of time series data. This enables using off-the-shelf machine learning tools to automatically cluster similar traces with respect to a given PSTL formula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 22 publications
0
58
0
Order By: Relevance
“…While this is useful, it is arguably even more useful to obtain higher-level interpretable insight into where the training data falls short, what new scenarios must be added to the training set, and how the learning algorithms' parameters must be adjusted to improve accuracy. For example, one could use techniques for mining specifications or requirements (e.g., [21,42]) to aggregate interesting test images or video into a cluster that can be represented in a high-level fashion. One could also apply our ML Analyzer outside the falsification context, such as for controller synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…While this is useful, it is arguably even more useful to obtain higher-level interpretable insight into where the training data falls short, what new scenarios must be added to the training set, and how the learning algorithms' parameters must be adjusted to improve accuracy. For example, one could use techniques for mining specifications or requirements (e.g., [21,42]) to aggregate interesting test images or video into a cluster that can be represented in a high-level fashion. One could also apply our ML Analyzer outside the falsification context, such as for controller synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Once mapped into this space, the signals can be subject to various learning and clustering algorithms as suggested recently in [41].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, preliminary exploration of this idea appeared in prior work by some of the co-authors in [16]. The key difference is the previous work required users to provide a ranking of parameters appearing in a signal predicate, in order to project time-series data to unique points in the parameter space.…”
Section: Related Workmentioning
confidence: 99%
“…While powerful, translating the knowledge of domain-specific experts into features remains a non-trivial endeavor. More recently, it has been shown that Parametric Signal Temporal Logic formula along with a total ordering on the parameter space can be used to extract feature vectors for learning temporal logical predicates characterizing driving patterns, overshoot of diesel engine re-flow rates, and grading for simulated robot controllers in a Massively Open Online Course [16]. Crucially, the technique of learning through the lens of a logical formula means that learned artifacts can be readily leveraged by existing formal methods infrastructure for verification, synthesis, falsification, and monitoring.…”
Section: Introductionmentioning
confidence: 99%